Recent progress in translational research on neurovascular and neurodegenerative disorders - Demuth, Hans-Ulrich; Dijkhuizen, Rick M.; Farr, Tracy D.; Gelderblom, Mathias; Horsburgh, Karen; Iadecola, Constantino; Mcleod, Damian D.; Michalski, Dominik; Murphy, Tim H.; Orbe, Josuna; Otte, Willem M.; Petzold, Gabor C.; et al. (IOS Press, 2017)
The already established and widely used intravenous application of recombinant tissue plasminogen activator as a re-opening strategy for acute vessel occlusion in ischemic stroke was recently added by mechanical thrombectomy, representing a fundamental progress in evidence-based medicine to improve the patient’s outcome. This has been paralleled by a swift increase in our understanding of pathomechanisms underlying many neurovascular diseases and most prevalent forms of dementia. Taken together, these current advances offer the potential to overcome almost two decades of marginally successful translational research on stroke and dementia, thereby spurring the entire field of translational neuroscience. Moreover, they may also pave the way for the renaissance of classical neuroprotective paradigms. This review reports and summarizes some of the most interesting and promising recent achievements in neurovascular and dementia research. It highlights sessions from the 9th International Symposium on Neuroprotection and Neurorepair that have been discussed from April 19th to 22nd in Leipzig, Germany. To acknowledge the emerging culture of interdisciplinary collaboration and research, special emphasis is given on translational stories ranging from fundamental research on neurode- and -regeneration to late stage translational or early stage clinical investigations.